Phenology, spatial distribution and development of sampling methods for Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) on snap beans and beans (Phaseolus vulgaris L.) - BUENO, JUAN MIGUEL; CARDONA, CÉSAR; CHACÓN, PATRICIA (Revista Colombiana de Entomología, 2005)
Trialeurodes vaporariorum is one of the most important and difficult to control pests of snap beans and dry beans in Colombia. To understand the distribution of the insect on the plant and the preferred feeding sites of immatures and adults, to quantify an action threshold previously established by CIAT, and to develop sampling methods, six trials were conducted in the field in the area of Pradera (Valle). In both snap beans and dry beans, adults colonize and oviposit on the young leaves, then migrate within the plant to the upper levels (strata) as the crop ages, while the nymphs and pupae are found on lower plant strata. Populations of the insect are affected by rainfall. A pattern of clumped distribution on the leaves was found for all stages of T. vaporariorum on snap beans and dry beans. For nymphs, a sample size of 50 leaflets taken at random on lower strata leaves was calculated. The recommended sampling patterns are in the form of an “M” or “Z” that encompass the borders. A sequential sampling plan was developed for first instar nymphs on snap beans based on an action threshold of 12 nymphs/2.25cm2 per leaflet.